2002
DOI: 10.1159/000063895
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Pattern in Blister Fluid and Sera of Patients with Pemphigus

Abstract: Background: Pemphigus is a chronic auto-immune blistering disease with four main variants, i.e. pemphigus vulgaris (PV), foliaceus (PF), erythematosus (PE) and vegetans. The common histological feature of this disease is acantholysis. Objective: The aim of this study was to compare levels of some cytokines in blister fluid and sera of patients with pemphigus, using as control blister fluid of patients with bullous pemphigoid (BP) and bullous contact dermatitis (BCD). Methods: Using an immuno-enzymatic assay (E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
27
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 18 publications
4
27
0
Order By: Relevance
“…Few studies have been undertaken to measure serum cytokine levels in patients with pemphigus [14,42,43]. In these studies, while IL-6 and TNF-α levels were increased, low to undetectable levels of IL-8 and IFN-γ were found in serum of pemphigus patients.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have been undertaken to measure serum cytokine levels in patients with pemphigus [14,42,43]. In these studies, while IL-6 and TNF-α levels were increased, low to undetectable levels of IL-8 and IFN-γ were found in serum of pemphigus patients.…”
Section: Discussionmentioning
confidence: 99%
“…The serum factors implicated in apoptolysis include Fas ligand (FasL) (14), tumor necrosis factor ␣ (15,16), interleukins 1, 6, 8, and 15 (15,(17)(18)(19), nitric oxide (9,20), kallikreins, and other proteases (21). Using an organ culture model of PV, it has been demonstrated that PVIgG works together with FasL and tumor necrosis factor ␣ to induce apoptolysis (22).…”
Section: Pemphigus Vulgaris (Pv)mentioning
confidence: 99%
“…The result of this study showed that although the mean level of IL-10 was higher in PV patients than controls but the difference was not significant. Barioni et al 18 reported that the IL-10 levels in the serum of PV patients are below the detection limits when compared to other skin diseases. On the contrary, Bhol et al 19 and D'Auria et al, 20 reported that increased levels of IL-10 have been detected in PV patients' serum compared to normal individuals and these cytokine levels correlate with severity of disease.…”
Section: Discussionmentioning
confidence: 99%
“…In this manner, it may limit the damage and prevent more extension of lesions in the skin and mucous membranes. 18,19 However, the increased levels of these cytokines in serum of PV patients compared to normal subjects might be according to the proinflammatory or immunoregulatory action of these molecules in this autoimmune and inflammatory disease. In addition, the results of this study may have significant utility in the evaluation of chemointerventional therapy.…”
Section: Discussionmentioning
confidence: 99%